How Does Economic Uncertainty Impact the Banking Sector Performance? Evidence from ASEAN - Muhammad Teguh Kuncoro; Izza Ashsifa (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
In recent years, global economic uncertainty has become a growing concern, particularly with the outbreak of the COVID-19 pandemic. Increased economic uncertainty significantly constrains bank risk, at some point weakening bank stability. This study examines and analyses solvency and liquidity on the firm performance of banking sector in ASEAN countries in the 2013-2022 period by economic uncertainty as a moderating variable. The samples obtained amounted to 1080. The results show that liquidity and economic uncertainty negatively affect firm performance. Solvency does not affect firm performance. Economic uncertainty as a moderation variable cannot moderate the effect of solvency on firm performance. Still, economic uncertainty can moderate (strengthen) the effect of liquidity on firm performance.